Protective properties of five newly synthesized cyclic compounds against sodium azide and N-methyl-N′-nitro-N-nitrosoguanidine genotoxicity - Turhan, Kadir; Ozturkcan, S. Arda; Turgut, Zuhal; Karadayi, Mehmet; Gulluce, Medine (SAGE PUBLICATIONS INC, 2012)
The current study aims to determine the antimutagenic potential of five newly synthesized cyclic compounds against the genotoxic agents sodium azide (NaN3) and N-methyl-N'-nitro-N-nitrosoguanidine (MNNG). The mutant bacterial tester strains were NaN3-sensitive Salmonella typhimurium TA1535 and MNNG-sensitive Escherichia coli WP2uvrA. According to the results, all the test compounds showed significant antimutagenic activity. The inhibition rates ranged from 26.05% (Compound 4-1 mu g/plate) to 68.54% (Compound 5-0.01 mu g/plate) for NaN3 and from 32.44% (Compound 3-1 mu g/plate) to 60.77% (Compound 5-1 mu g/plate) for MNNG genotoxicity. Moreover, the mutagenic potential of the test compounds was investigated using the same strains. The results showed that all the test compounds do not have mutagenic potential on the bacterial strains at the tested concentrations. Thus, the findings of the present study give valuable information about chemical prevention from NaN3 and MNNG genotoxicity.
Keywords: Synthetic cyclic compounds; antimutagenicity; mutagenicity; bacterial reverse mutation test; MNNG; sodium azide; ONE-POT SYNTHESIS; POLYHYDROQUINOLINE DERIVATIVES; ANTIMUTAGENIC ACTIVITY; MANNICH REACTION; MUTAGENESIS; CHEMISTRY; EXTRACT; KETONES; ASSAY; Public, Environmental & Occupational Health; Toxicology